Global liquidity models, indicators, and indices: challenges, current state, and opportunities - Chaban, Andrii (Здобутки економіки: перспективи та інновації, 2025)
In the current context of global financial instability, the issue of assessing the level of global liquidity is gaining particular relevance, both in theoretical and applied dimensions. Global liquidity is a key factor influencing the scale and direction of monetary transmission, shaping the conditions for banking system resilience, regulating access to capital, and affecting the cyclicality of financial markets. However, the absence of a unified indicator, methodological inconsistencies, and fragmented data availability complicate the quality of macroeconomic analysis. The purpose of this article is to systematize approaches to measuring global liquidity, identify methodological features of leading indicators, and test a practical example: the global liquidity index developed by the Bank for International Settlements (BIS), based on aggregated credit in U.S. dollars to the non-bank sector. Methods. The study applies methods of structural-logical analysis, content analysis of analytical and statistical sources, and elements of comparative evaluation of indicators based on BIS data. Special attention is paid to series Q.USD.3P.NAIDUSD, which reflects the volume of cross-border and local credit in U.S. dollars granted to non-bank entities worldwide. The results of the analysis indicate that the most relevant source for assessing global financial liquidity is the combination of indicators that integrate data on both banking credit and debt securities. The chosen BIS series demonstrates a significant expansion of global USD liquidity from 2020 to 2022, driven by highly accommodative monetary policy, and its contraction from 2023 to 2024 amid the global interest rate tightening cycle led by major central banks. Conclusions. The current methodological approach to the global liquidity framework requires further harmonization, particularly through the integration of monetary and financial liquidity indicators, the inclusion of digital assets, and consideration of the fiscal context. Future research should focus on developing a synthetic global liquidity index with high sensitivity to financial shocks.